Still foolin' 'em eaudiobook Where i've been, where i'm going, and where the hell are my keys?. - Crystal, Billy (Macmillan Audio, 2013)
Nominated for a 2014 Grammy in the Spoken Word category! Hilarious and heartfelt observations on aging from one of America's favorite comedians, now that he's 65, and a look back at a remarkable career. Billy Crystal is 65, and he's not happy about it. With his trademark wit and heart, he outlines the absurdities and challenges that come with growing old, from insomnia to memory loss to leaving dinners with half your meal on your shirt. In humorous chapters like "Buying the Plot" and "Nodding Off," Crystal not only catalogues his physical gripes, but offers a road map to his 77 million fellow baby boomers who are arriving at this milestone age with him. He also looks back at the most powerful and memorable moments of his long and storied life, from entertaining his relatives as a kid in Long Beach, Long Island, and his years doing stand-up in the Village, up through his legendary stint at Saturday Night Live, When Harry Met Sally, and his long run as host of the Academy Awards. Listeners get a front-row seat to his one-day career with the New York Yankees (he was the first player to ever "test positive for Maalox"), his love affair with Sophia Loren, and his enduring friendships with several of his idols, including Mickey Mantle and Muhammad Ali. He lends a light touch to more serious topics like religion ("the aging friends I know have turned to the Holy Trinity: Advil, bourbon, and Prozac"); grandparenting; and, of course, dentistry. As wise and poignant as they are funny, Crystal's reflections are an unforgettable look at an extraordinary life well lived. Still Foolin' 'Em includes a portion recorded in front of a live studio audience.